Pressão arterial e reatividade vascular em frangos de corte machos de cinco linhagens comerciais - Gonzales, Elisabeth [UNESP]; Macari, Marcos [UNESP]; Junqueira, Otto Mack [UNESP]; Rosa, Guilherme J.M. [UNESP] (My University, 1998)
Blood pressure and vascular reactivity to phenylephrine (hypertensor) and sodium nitroprusside (hypotensor) was determined on male broilers taken from 5 commercial strains (Arbor Acres, Cobb, Hubbard-Peterson, ISA and Ross), with 21-28 days of age. Blood pressure was measured in the femoral artery by introducing a cannula attached to a pressure transdutor and recorded on a polygraph. Hyper or hypopressor substances were injected via jugular vein at 5, 10, 20 and 40-mcg kg-1 body weight. No differences in the systolic, diastolic and mean blood pressure and no significant blood pressure responses to phenylephrine and sodium nitroprusside were observed among strains. Throughout strain and treatment blood pressures (systolic, diastolic and mean) were high in both experiments. This suggests that these modern male broilers have high arterial pressure possibly due to an indirect selection effect.
Blood pressure and vascular reactivity of male broilers from five commercial strains
Keywords: Blood pressure; Broilers; Males; Strains; Vascular reactivity